The Mangakkai’ Ceremony in Aluk To Dolo: Analysis Based on Victor Turner's Perspective and Its Relevance to Human Relation - Agustinus Abraham (FKIP, Universitas Palangka Raya, 2026)
This study analyzes the mangakkai’ ceremony in the Aluk To Dolo tradition in the villages of Suppiran, Mesakada, and Salisali (SMS), Toraja, as a rite of passage that has religious, symbolic, and social meanings. The study aims to explain the structure of the mangakkai’ ritual based on Victor Turner's theory of liminality and to examine its relevance to contemporary human relations. The method used is qualitative research with a literature study approach enriched by field interviews with Aluk To Dolo figures. The results of the study show that mangakkai’ consists of three main stages, namely pre-liminal (lao ma’tundan) as a phase of separation, liminal (passurusan and mata kandean) as a space for community formation, and post-liminal (ma’palulangngan) as reintegration and refinement of relations with Puang Matua. This rite not only guides the soul of the deceased to a transcendent destination, but also strengthens solidarity, mutual cooperation, and the transmission of values between generations. In a modern context marked by individualism and social fragmentation, mangakkai’ presents a model of relationships based on togetherness, empathy, and collective responsibility. Thus, this ritual has anthropological and ethical significance as a source of reflection for the formation of more humanistic and communal human relationships.